Scientific Club of Evidence-Based Practice in the management of wounds: an innovative educational tool for enterostomal therapy - Freitas, Paula de Souza Silva; Santos, Anna Bárbara de Almeida dos; Souza, Karen Montuan de; Ramalho, Aline de Oliveira; Moraes, Juliano (Estima – Brazilian Journal of Enterostomal Therapy, 2025)
Objective: To describe the creation and results of the “Scientific Club of Evidence-Based Practice in the management of hard-to-heal wounds” as a tool to disseminate the best care strategies in the field of enterostomal therapy. Method: This is a reflective report of an experience with a qualitative approach, detailing the creation of a club to discuss consensuses related to hard-to-heal wounds, as part of a university extension project for the nursing course at a public university in Espírito Santo, between June 2022 and August 2023. Nursing students, general nurses, dermatologists, and stomatherapists from all over Brazil participated in the study. Results: The Scientific Club operated for free and had 1,598 subscribers, with 13 synchronous meetings, one every month. Participants received the study material and had the opportunity to discuss the main recommendations of the consensus with an expert on the subject. At the end of the cycle, a certificate of participation was issued to those who obtained satisfactory performance, measured through questionnaires with multiple choice questions about each topic. Conclusion: The Scientific Club can be an innovative tool for nursing education in enterostomal therapy, providing information on the best available evidence about wound care.